Mole Crickets, Scapteriscus spp. - John L. Capinera; Norman C. Leppla (EDIS, 2002)
This document is EENY-235, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2001.